Methyl-Coenzyme M Reductase and Its Post-translational Modifications - Chen, Hao; Gan, Qinglei; Fan, Chenguang (Frontiers in Microbiology, 2020)
The methyl-coenzyme M reductase (MCR) is a central enzyme in anaerobic microbial methane metabolism which consists of methanogenesis and anaerobic oxidation of methane (AOM). MCR catalyzes the final step of methanogenesis and the first step of AOM to achieve the production and oxidation of methane, respectively. Besides a unique nickel tetrahydrocorphinoid (coenzyme F430), MCR also features several unusual post-translational modifications (PTMs) which are assumed to play important roles in regulating MCR functions. However, only few studies have been implemented on MCR PTMs. Therefore, to recapitulate current knowledge and prospect future studies, this review summarizes and discusses studies on MCR and its PTMs.